Does the gender diversity of the Board of Commissioners, Family Ownership, and Institutional Ownership Reduce the Likelihood of Financial Distress During COvid-19? - Alief Ibnu Nuzul; Vera Diyanty (UNIVED Press, 2024)
The purpose of this study is to investigate the effect of the gender diversity of the board of commissioners, family ownership, and institutional ownership on the possible financial distress of Indonesian public manufacturing companies during the COVID-19 pandemic and non-pandemic periods. This study uses logistic regression panel data to determine the effect of the three aspects of Corporate Governance (CG) studied on financial distress. A total of 648 company-year observations from 108 companies during the period 2017-2022 were used in the analysis. Research findings indicate that in non-pandemic periods, family ownership has a positive effect on financial distress, but the positive effect decreases during pandemic periods. Institutional ownership has a negative influence in the non-pandemic period and that influence has not changed during the pandemic period. Meanwhile, the gender diversity of the board of commissioners does not affect financial distress in either the pandemic period or the non-pandemic period. This report provides insights for company management and regulators in developing CG mechanisms, especially related to the board of commissioners' gender diversity, family ownership, and institutional ownership.